Moderator Effect of Technological Advancement on Financial Development and Economic Growth Nexus in Asian Countries - Hewage, Rishan Sampath; Pyeman, Jaafar; Othman, Norashida (Universiti Utara Malaysia Press, 2024)
The examination of the nexus between Financial Development (FD), Technological Advancement (TA), Human Capital (HC), and Private Consumption (PC) to Economic Growth (EG) has gained substantial attention in both empirical and theoretical academia since the early nineteenth century. Scholars affirm that FD, HC, PC, and TA are crucial factors in determining optimal resource allocation and efficient utilization required to achieve sustainable EG. This study investigates the nexus of FD, HC, and PC with EG in Asian countries, with TA serving as the moderator. Data from 35 countries were collected annually over 15 years, spanning from 2005 to 2019. Using short panel data analysis, due to the higher number of crosssections (35) compared to time intervals (15), the findings confirm TA’s significant moderator effect in both short and long-run time scenarios. Additionally, a significant negative relationship with EG is observed for FD and PC, while TA and HC are identified as promoters of EG. The study underscores the importance of investing in TA while concurrently developing the quality of the labor force. Policymakers are encouraged to prioritize technology development and the introduction of innovative techniques. However, caution is advised in FD projects, necessitating strategies to reduce domestic private consumption